Efficacy of the Danish epilepsy surgery programme. (10th October 2017) - Holm, E.; Foged, M. T.; Beniczky, S.; Jespersen, B.; Brennum, J.; Pinborg, L. H.
Abstract : Objective: Despite optimal medical treatment, approximately one‐third of patients with epilepsy continue to have seizures. Epilepsy surgery is widely accepted as a therapeutic option in the selected subset of patients with drug‐resistant focal epilepsy. Here, we report the results of the Danish epilepsy surgery programme from 2009 to 2014. Material and methods: A total of 169 consecutive patients, operated at Rigshospitalet, were included. Information was gathered from digital patient records. Before 1‐year follow‐up, two patients were lost to follow‐up and three were referred to new surgery. Results: The median years of drug resistance before operation were 11 years. At 1‐year follow‐up (n = 164), seizure outcomes were as follows: 65% Engel I (free from disabling seizures), 51% Engel IA (completely seizure free) and 9% Engel IV (no worthwhile improvement), and for patients operated in the medial temporal lobe (n = 114): 70% Engel I, 56% Engel IA, 5% Engel IV. The outcomes of the 53 patients needing intracranial EEG recording (ICR) were not significantly different from the patients only evaluated with surface EEG. None of the eight MRI‐negative patients operated outside the medial temporal lobe after ICR were free of disabling seizures. 12% of MTLE patients developed de novo depression after epilepsy surgery despite good surgical outcome. Three patients required rehabilitation due to post‐operative hemiplegia. Conclusion: The outcomes of the Danish epilepsy surgery programme align with international results found in recent meta‐analyses. Serious complications to epilepsy surgery are seldom. In accordance with international recommendations, Danish drug‐resistant patients should be referred to epilepsy surgery evaluation at an earlier stage of the disease.